El presupuesto COVID en la calidad de gasto público de la unidad ejecutora 406 red de salud Huancavelica: periodo 2020 – 2021 - Melchor Acevedo, Braulio (2023)
The objective of this research is to determine the relationship between the Covid Budget and the Quality of Expenditure in the Executing Unit 406 Red de Salud Huancavelica during the period 2020-2021. A descriptive-correlational quantitative approach was used, with the Covid Budget and the Modified Institutional Budget being significant variables, while the Accrued Phase is not. In conclusion, there is a direct and significant relationship between the Covid Budget and the Quality of Expenditure in medical care in the province of Huancavelica